2016
DOI: 10.1002/2016jd025188
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of recent theories to understand cyclogenesis pathways of tropical cyclone Madi (2013)

Abstract: The present study aims to examine the new understanding of cyclogenesis by analyzing the genesis sequence of formation of a very severe cyclonic storm Madi (6–13 December 2013) that occurred over the Bay of Bengal. We have generated a high‐resolution (18 km, 6 km, and 2 km) analysis using three‐dimensional variational data assimilation technique and Weather Research and Forecasting model. The genesis sequence of Madi cyclone is analyzed using the concepts in the marsupial theory and other theories of tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 76 publications
(162 reference statements)
1
18
0
Order By: Relevance
“…Figures a–f show the composite trueθ̇ structure of TCs in ERAI, GFS, JRA55, MERRA2, CFSR, and ERA5 data sets, respectively. The trueθ̇ values captured in all reanalysis data sets are in range from −1.5 K(6 hr) −1 to +1.5 K(6 hr) −1 which are very low in comparison with the estimated value of trueθ̇ (Wang, ; Rajasree, Kesarkar, Bhate, Singh, et al, ; Rajasree, Kesarkar, Bhate, Umakanth, et al, ). The pattern of increase in diabatic heating in the inner core region of TCs with intensification is represented more correctly in GFS analysis (Figure b) and CFSR (Figure e) followed by ERA5 (Figure f) data set compared to other data sets.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Figures a–f show the composite trueθ̇ structure of TCs in ERAI, GFS, JRA55, MERRA2, CFSR, and ERA5 data sets, respectively. The trueθ̇ values captured in all reanalysis data sets are in range from −1.5 K(6 hr) −1 to +1.5 K(6 hr) −1 which are very low in comparison with the estimated value of trueθ̇ (Wang, ; Rajasree, Kesarkar, Bhate, Singh, et al, ; Rajasree, Kesarkar, Bhate, Umakanth, et al, ). The pattern of increase in diabatic heating in the inner core region of TCs with intensification is represented more correctly in GFS analysis (Figure b) and CFSR (Figure e) followed by ERA5 (Figure f) data set compared to other data sets.…”
Section: Resultsmentioning
confidence: 96%
“…It is speculated that the majority of the errors in the spatiotemporal representation of development of TCs are mainly due to the coarse resolution of reanalysis data sets and unknown physical processes that contribute to the evolution of TCs and their parameterization in NWP. However, reanalyses developed based on high‐resolution mesoscale models are more in agreement with IMD best track data sets (Rajasree, Kesarkar, Bhate, Singh, et al, ; Rajasree, Kesarkar, Bhate, Umakanth, et al, ). Therefore, it can be said that there is a need to develop a high‐resolution global reanalysis data set that can represent the spatiotemporal evolution of TCs more appropriately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is the second part of our study aimed to understand cyclogenesis pathways over the North Indian Ocean (NIO). Our previous study [ Rajasree et al ., ] examined the genesis pathway of tropical cyclone Madi that occurred over the Bay of Bengal (BoB) during 6–13 December 2013. This study showed that the genesis of tropical cyclone Madi follows the hypotheses of the marsupial paradigm even though the original formulation of the marsupial paradigm were based on the dynamics of easterly waves generated along the African Easterly Jet (AEJ) which move across the Atlantic Ocean (AO).…”
Section: Introductionmentioning
confidence: 99%
“…Rajasree et al . [] found that the precursor disturbance of tropical cyclone Madi originated from a Westward Moving Disturbance (WMD) embedded in the Intertropical Convergence Zone (ITCZ). The pouch region associated with the parent disturbance played a major role in the vorticity upscaling and aggregation of moisture inside it.…”
Section: Introductionmentioning
confidence: 99%